A Problem-Posing-Based Critical Literacy Pedagogy Model for Developing Critical Reading Skills among Pre-Service Indonesian Language Educators - Intan Ramdhani; Sumiyani Sumiyani (Journal of General Education and Humanities, 2026)
Despite the demand for 21st-century skills, literacy is rarely addressed as a transformative power to challenge social structures, and many pre-service teachers still lack sufficient critical reading competence. This study aims to analyze the core conceptual framework of Critical Literacy Pedagogy (CLP) and validate the effectiveness of the problem-posing model in developing the critical reading skills of pre-service Indonesian language educators. The study utilizes a concept analysis and an integrative review design, synthesizing Paulo Freire’s philosophical foundations with empirical validation. The empirical data, adapted from relevant quasi-experimental studies involving 56 pre-service teachers, indicate that the problem-posing model has a highly significant effect (p < 0.005) on all six sub-skills of critical reading. The most substantial improvements were observed in Explanation (F=96.898) and Analysis (F=65.202), signifying a successful pedagogical shift from passive "banking education" to autonomous social agency and higher-order thinking. The study concludes that the Problem-Posing based CLP model is a transformative approach that empowers pre-service teachers to interrogate dominance within texts. It is essential to integrate CLP into teacher education curricula to prepare educators as agents of social change who can navigate the complexities of modern discourse and digital disinformation.